Diagnostic Utility of High Fluorescence Cells in Detecting Malignant Effusions - Shashank Mishra; Biren P. Parikh; Jayvardhan Singh (Journal of Cytology, 2024)
Background: Most modern haematology analysers have a dedicated body fluid mode for cell counts of body fluids. Many analysers also count the number of high fluorescence cells (HF cells). HF cells have a large nuclear size and emit high fluorescence when stained with fluorescent dyes. Due to their large nuclear size, Malignant cells are counted as HF cells. Aims and Objectives: We aim to determine the diagnostic utility of HF cells in predicting the presence of malignant cells in serous effusions. Materials and Methods: HF cell counts were done on 209 serous fluid samples using the body fluid mode of Mindray BC-6800 plus haematology analyser. Papanicilaou-stained smears of all samples were examined for the presence of malignant cells by a panel of cytopathologists. ROC curve analysis was done to determine the sensitivity and specificity of HF cells in malignant effusions. Results: Out of 209 samples, malignant cells were found by microscopy in 97 cases (46.4%). The absolute number and percentage of HF cells were significantly higher (P < 0.001) in malignant effusions (HF# = 24.9 cells/ul, HF% = 10.4%) when compared to non-malignant samples (HF# = 4.95 cells/ul, HF% = 5.76%). ROC curve analysis determined an optimal cut-off of ≥30 HF cells/ul (sensitivity = 73.91, specificity = 55.66%) for the prediction of malignant cells. Conclusion: HF cells in serous effusions can be a helpful tool to aid the pathologist, but it is not an ideal screening test due to its low sensitivity (67.74%) and negative likelihood ratio (0.5) at a cut-off of ≥30 HF cells/ul. However, due to high specificity of 83.18% at a cut-off of ≥72 HF cells/ul, a meticulous search for malignant cells should be done on microscopy.